(untitled) (Tanzania Journal for Population studies and Development, 2020)
Community-Based Health Insurance schemes are meant to expand the coverage of healthcare provision to, especially, the majority poor in the rural areas of the Developing World. Despite high sensitization and mobilization campaigns, enrolment, re-enrolment and utilization of such schemes have been unexpectedly low. This is also the case with the Redesigned Community Health Fund (rCHF) in Tanzania. We took a qualitative approach to explore the reasons for the drop-outs of the rCHF in Mpwapwa District in central Tanzania. We reviewed various rCHF-related documents and used Key Informant Interviews and Focused Group Discussions to collect data from randomly selected drop-out cases. The findings suggest the availability of drugs, premium costs, quality of healthcare facilities as key reasons influencing households to enrol, re-enrol or drop-out of the rCHF. In this paper we argue that rCHF should integrate more participatory approaches to understand local concerns and re-design the scheme to address the challenges. Keywords: Drop-outs; Community Based Health Insurance; rCHF Community-Based Health Insurance schemes are meant to expand the coverage of healthcare provision to, especially, the majority poor in the rural areas of the Developing World. Despite high sensitization and mobilization campaigns, enrolment, re-enrolment and utilization of such schemes have been unexpectedly low. This is also the case with the Redesigned Community Health Fund (rCHF) in Tanzania. We took a qualitative approach to explore the reasons for the drop-outs of the rCHF in Mpwapwa District in central Tanzania. We reviewed various rCHF-related documents and used Key Informant Interviews and Focused Group Discussions to collect data from randomly selected drop-out cases. The findings suggest the availability of drugs, premium costs, quality of healthcare facilities as key reasons influencing households to enrol, re-enrol or drop-out of the rCHF. In this paper we argue that rCHF should integrate more participatory approaches to understand local concerns and re-design the scheme to address the challenges.